2014
DOI: 10.1007/s11356-014-3672-3
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of chlorinated volatile organic compounds emitted from office printers and photocopiers

Abstract: Office devices can release volatile organic compounds (VOCs) partly generated by toners and inks, as well as particles of paper. The aim of the presented study is to identify indoor emissions of volatile halogenated organic compounds into the office workspace environment. Mixtures of organic pollutants emitted by seven office devices, i.e. printers and copiers, were analyzed by taking samples in laboratory conditions during the operation of these appliances. Tests of volatile organic compound emissions from se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 30 publications
1
13
0
2
Order By: Relevance
“…The use of various metal/metal oxide ENPs similar to those found in toners and PEPs, such as iron, manganese, titania, zinc and copper have been known to have enhanced catalytic properties due to the increased reactivity and selectivity of these metallic particles (41,4346). It is also worth noting that other particle formation mechanisms involving ozone, in addition to the nano scale metal and metal oxide particles added and released form the toners during printing, have been proposed in previous studies and may also contribute to this VOC transformation phenomenon taking place and reported in this study [(14, 59). …”
Section: Resultssupporting
confidence: 55%
“…The use of various metal/metal oxide ENPs similar to those found in toners and PEPs, such as iron, manganese, titania, zinc and copper have been known to have enhanced catalytic properties due to the increased reactivity and selectivity of these metallic particles (41,4346). It is also worth noting that other particle formation mechanisms involving ozone, in addition to the nano scale metal and metal oxide particles added and released form the toners during printing, have been proposed in previous studies and may also contribute to this VOC transformation phenomenon taking place and reported in this study [(14, 59). …”
Section: Resultssupporting
confidence: 55%
“…Also, the emissions of ozone and VOC produced through the laser printers were significantly higher than ink-jet printers. In another study, Kowalska, Szewczyńska, and Pośniak (2015) analysed the indoor emissions of volatile halogenated organic compounds (VHOCs) produced through office printers and copiers by taking samples in laboratory conditions during the operation of these appliances. The tests of VHOCs were performed by dint of utilizing a simulated environment (test chamber).…”
Section: Sbs Contributors Symptoms and Effectsmentioning
confidence: 99%
“…[The maximum detected styrene concentration in a U.S. copy center in the late 1990s, 12.8 µg/m 3 (Stefaniak et al 2000) is also well below the U.S. EPA's current (June 2017) Regional Screening Level for industrial air, 4400 µg/m 3 (U.S. EPA, 2017b)]. Several studies indicated that styrene emissions from photocopiers are higher than those from printers (with emissions from laser printers exceeding those from inkjet printers and multifunctional devices) and computers (CARB, 2011;Destaillats et al 2008;Kowalska, Szewczyńska, and Pośniak 2015). While emissions from computers decreased with age, those from printers did not (presumably because toner is the primary source) (CARB, 2011;Destaillats et al 2008).…”
Section: Indoor Airmentioning
confidence: 96%